Transforming Minimum Wage Policy Toward a Living Wage in Indonesia’s Hospitality Industry: A Multipol Analysis - Sukamdani, Hariyadi B.; Ariyani, Nafiah (Yayasan Sinergi Kawula Muda, 2026)
This study develops a strategic framework for transitioning from a minimum wage to a living wage system in the Indonesian hospitality sector. Utilizing the MULTIPOL multicriteria analysis, the research evaluates the strategic hierarchy of policy scenarios, examines the consistency between interventions and actions, and constructs a conceptual transformation roadmap. Findings reveal that Productivity Enhancement (P3) is the most influential and resilient policy framework, followed by Variable Income Transparency (P1) as a critical stabilizing anchor. These policies demonstrate high resilience across various future scenarios, particularly under Gradual Fair Transformation (S4). Correspondence mapping further identifies a strong strategic fit between productivity-driven policies and Productivity Training (A6), while aggressive base-wage hikes are found to be highly context-sensitive. The study concludes with a strategic transformation flowchart, proposing a multi-track approach: a Primary Track (productivity-led), a Baseline Track (transparency-focused), and a Contingent Track (adaptive social dialogue). This research shifts the wage discourse toward an